IMPLEMENTASI FRAMEWORK DELONE DAN MCLEAN UNTUK MENGUKUR KEPUASAN DAN KEAMANAN PADA PENGGUNA APLIKASI M-BANKING - Winson Winson; Darmansah Darmansah (Computer Science and Industrial Engineering, 2026)
The development of digital technology has transformed conventional banking services into application-based services, one of which is mobile banking. MyBCA Mobile is the latest application from Bank Central Asia that offers various modern features, but still faces user complaints regarding system stability, slow OTP (On-Time Transaction) requests, and login issues. This condition necessitates a more in-depth evaluation of user satisfaction and perceived security. This study uses the Information System Success Model framework from DeLone & McLean with the addition of a security dimension to measure system quality, information quality, service quality, user satisfaction, and perceived net benefits. The research method used is quantitative, through the distribution of questionnaires to MyBCA Mobile users. Data were analyzed using validity and reliability tests, and multiple linear regression analysis. The results show that system quality, service quality, and security have a significant effect on user satisfaction, while information quality and usage have no significant effect. User satisfaction has been shown to have a significant effect on net benefits. The conclusion of this study indicates that system stability, service quality, and security are the main factors in increasing satisfaction and perceived benefits of using MyBCA Mobile.